Key Factors Influencing Behavioral Changes in Hypertensive Clients at the Integrated Development Post for Non-Communicable Diseases - Zebua, Fasman; Badiran, Muhammad; Anto, Anto (Jurnal Perilaku Kesehatan Terpadu, 2024)
The rising prevalence of hypertension in South Nias Regency, particularly within the UPTD working area of Lolowau Health Center, has become a critical public health concern. POSBINDU (Integrated Development Post for Non-Communicable Diseases) services are underutilized, despite being vital for early detection and management of hypertension. This study aims to identify the key factors influencing behavioral changes in hypertensive clients attending POSBINDU within this region. A cross-sectional quantitative research design was employed, gathering data from 45 hypertensive clients registered at the Lolowau Health Center. Data were collected through structured questionnaires and analyzed using multiple linear regression and chi-square tests to determine significant relationships between variables such as knowledge, attitude, employment status, family support, and health worker information. The results revealed that knowledge (p = 0.014), attitude (p = 0.033), employment status (p = 0.011), family support (p = 0.003), community leader support (p = 0.023), and health worker information (p = 0.009) were significantly associated with behavior changes among hypertensive clients. Notably, family support emerged as the most influential factor in promoting positive behavior change, with an Exp B value of 12.346. These findings underscore the importance of enhancing family involvement, improving health worker communication, and fostering community leadership to increase the engagement of hypertensive clients with POSBINDU services. Strengthening these factors can lead to more effective hypertension management and improved health outcomes within the community.